Hubungan Antara Pengetahuan Dan Kepatuhan Ibu Hamil Dalam Mengkonsumsi Tablet Fe Dengan Kejadian Anemia Ibu Hamil Di Puskesmas Weru - Sulasmi, Sri; , Elida Soviana, S.Gz., M.Gizi (2016)
Background : Anemia is one of health problems that happens in pregnant mothers. Some factors that influence it are knowledge and obedience in consuming Fe tablet. In Primary Health Care Of Weru the number of anemia in pregnant mothers increased from 5,98% in 2014 to 6,45% in 2015 Objective : To understand of the relationship between knowledge and obedience of pregnant mothers in consuming Fe tablet with anemia in pregnant mothers at Primary Health Care of Weru Method :Descriptif analytic use design cross sectional. Quota sampling method with 49 subject is the method to take the sample . The questioner method is used to take the knowledge and obidience and check up the Hb in anemia happened. The data analisys use chi square Result : The result from 49 subject that has good knowledge is 59,2% not good is 40,8% and abay to consumtion Fe tablet 63,3% and not abay is 36,7%. The anemia happen is 30,6% and not 69,4%.The number of p in the relationship of knowledge and anemia happen is 0,014 with OR 0,208 (95% 0,057-0,766) and p for the relationship of obedience and happen is 0,025 with OR 0,240 (95% CI 0,066-0,866) Summary : There is a relation of knowledge with anemia case and relation to between obedience to consumtion of Fe tablet and anemia case Keywords : knowledge,obedience, anemia Bibliografi : 25 : 2002-2014